Radiologic Evaluation of Compressive Osseointegration for the Fixation of Reconstruction Prostheses after Tumor Resection. (22nd July 2015) - Lazarov, Manol; De Bo, Thomas; Poffyn, Bart; Sys, Gwen
Abstract : Objective . In pursuance of thoroughly understanding and facilitating the evaluation of the radiological changes in the preloaded bone by Compliant Pre-Stress osseointegration (Compress Biomet, Warsaw, Indiana) a new staging method was created depicting four stages. Methods . Two cohorts (10 and 17 patients resp., not-receiving and receiving chemotherapy) were compared in terms of progression of osseointegration. Based on the changes at the bone-metal interface seen on röntgenorgrams four stages were defined: stage 0: immediate postoperative status, no ingrowth, or noncalcified callus; stage 1: early mineralization, calcified callus; stage 2: mature mineralization; and stage 3: hypertrophy at the level of the pins. Results . There were no significant differences between the two cohorts. Group 2, which was significantly younger than group 1 (p < 0.001 ), presented a delayed initial rate of bone formation and reached stage 1 at 6 months instead of 3 months like group 1. The children from the group 2 demonstrated a visible rebound ingrowth. Conclusion . Despite the fact that the staging fails to demonstrate a statistical difference, it is rather simple and can be used for future studies.